Energy band gap and electrical conductivity of Cd₁₋xMnxTe alloys with different manganese content - Kosyachenko, L.A.; Rarenko, I.M.; Aoki, T.; Sklyarchuk, V.M.; Maslyanchuk, O.L.; Yurtsenyuk, N.S.; Zakharuk, Z.І. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The optical and electrical properties of single Cd₁₋xMnxTe (x = 0.07 - 0.40) crystals with p-type conduction and resistivity 10⁴– 10⁸ Ohm⋅cm have been studied. The band gaps of the samples and their temperature dependences have been determined. The electrical conductivity of this material and its temperature variation are explained in terms of statistics for electrons and holes in semiconductor with taking into account the compensation process. The energy of ionization and degree of compensation levels responsible for the electrical conductivity of the samples have been found.